COMMUNICATION STRATEGIES IN TABANAN NYENTANA COUPLES RELATED TO GENDER DIFFERENCE AND MATRILINEAL MARRIAGE SYSTEM - Wulandari, Ni Putu Desi; Padmadewi, Ni Nyoman; Budasi, I Gede (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study is aimed at determining the communication strategies used by Nyentana couples in Tabanan regency. The study was designed in the form of qualitative research in which all research results were analyzed descriptively. Participant observation and interview were used as the methods to obtain data in this study, while the observation sheets and interview blueprint were used as the instruments. Four Nyentana couples in Tabanan regency were selected as the subjects of this study by using purposive sampling technique. It was found that the couples used several kinds of communication strategy, such as (1) imperative form of speech, (2) the forms of the question, and (3)Â  silence. It was also found that wives in marriage Nyentana expressed indirect utterances and did silence as communication strategy more often than their husbands. While the discussion of the consequences that occured due to communication strategies expressed or done by each participant is that obedience and rejection are the reciprocal effect of Imperative speeches, whereas rejection and anger occured as the reciprocal effect of the silence. As for the questions that have hidden motives behind them; obedience, agreement and rejection happened in return. Key words: nyentana marriage system, communication strategies, matrilineal marriage.